Answer:the anewer is
Step-by-step explanation:
54.4 dollars
Answer:
(f.g)(x)=4x^3+4x^2
Step-by-step explanation:
f(x) = 4x^2and g(x) = x+1, (f•g)(x)=?
(f.g)(x)=f(x)*g(x)
(f.g)(x)=4x^2*(x+1)
(f.g)(x)=4x^3+4x^2
hope it helps. .brainliest please
(d): y = mx+n
m = -2/3 ⇒ y = (-2/3)x +n
A(-4, 6) ∈ d ⇒ 6 = (-2/3)·(-4) +n ⇒ 6 = 8/3 +n ⇒
⇒ n = 6 - 8/3 ⇒ n = 10/3
Now, we have:
y = (-2/3)x +10/3
Graph the equation in a graphing calculator or in the table in a regular calculator and look for the zero on the x axis and the y axis
Answer:
X= 18
CBD= 47
Step-by-step explanation: